2023
DOI: 10.1097/gh9.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Devastating earthquake in Turkey: a call for global action

Abstract: An earthquake is a natural phenomenon like wind and rain. It is a sudden and rapid shaking of the earth caused by the release of energy stored in rocks. Earthquakes have occurred for billions of years in some parts of the world, especially in African, European, and Mediterranean regions. Many stories along the history of man show the considerable impact they have had on human lives and property. Earthquakes are the most terrifying and destructive among the other natural phenomena like rain or wind [1] . A coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…in an implementable way. Research studies have shown that awareness campaigns can go a long way in mitigating health issues and other environmental problems, for example, flooding [1,29,34,39] . Research has shown that flooding is a risk factor for waterborne and vector-borne diseases, for example, Malaria [2] .…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…in an implementable way. Research studies have shown that awareness campaigns can go a long way in mitigating health issues and other environmental problems, for example, flooding [1,29,34,39] . Research has shown that flooding is a risk factor for waterborne and vector-borne diseases, for example, Malaria [2] .…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…All over the world, flooding is known to cause significant damage to people's lives, belongings and properties [25] . Statistics show that flooding causes one-third of deaths, one-third of all injuries and one-third of all damage from natural disasters, such as earthquakes [1,22,25] . The scale of the impact of flooding is dependent upon the vulnerability of the environment and the local population, and the people living in Buea are particularly susceptible to the adverse outcomes.…”
Section: Impacts Of Flooding On Healthcare In Buea Citymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we recommend the World Medical Association (WMA) in partnership with respective medical associations worldwide such as; the National Medical Associations (NMA), including Medical Students Associations (MSAs) to deploy medical experts, health volunteers, medical students, nurses, psychologists, social workers, etc 11 ,. to Sudan as soon as possible to treat the injured individuals as well providing psychological supports to the affected victims, therein, prevent further injuries and complications as a result of the crisis.…”
mentioning
confidence: 99%
“…Furthermore, we recommend the World Medical Association (WMA) in partnership with respective medical associations worldwide such as; the National Medical Associations (NMA), including Medical Students Associations (MSAs) to deploy medical experts, health volunteers, medical students, nurses, psychologists, social workers, etc. [11] , to Sudan as soon as possible to treat the injured individuals as well providing psychological supports to the affected victims, therein, prevent further injuries and complications as a result of the crisis. Also, various nongovernmental organizations and Amnesty organizations and philanthropists the world should provide relief aid, palliations as well as moral supports, etc., for the Sudanese during this hardship as these would go a long way to restore their lost healthy state.…”
mentioning
confidence: 99%